2022
DOI: 10.1021/acs.bioconjchem.2c00142
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Three Azide-Modified Disaccharide Oxazolines as Enzyme Substrates for Single-Step Fc Glycan-Mediated Antibody-Drug Conjugation

Abstract: Antibody-drug conjugates (ADCs) hold great promise for targeted cancer cell killing. Site-specific antibody-drug conjugation is highly desirable for synthesizing homogeneous ADCs with optimal safety profiles and high efficacy. We have recently reported that azide-functionalized disaccharide oxazolines of the Manβ1,4GlcNAc core were an efficient substrate of wild-type endoglycosidase Endo-S2 for Fc glycan remodeling and conjugation. In this paper, we report the synthesis and evaluation of new disaccharide oxazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, either for the GTase-based or for the ENGase-based one, these approaches are restricted in substrate synthesis and dependent on two or more enzymes, a quite complicated and challenging procedure. To solve this issue, Wang et al, as well as our group, reported the one-step strategy for gsADCs assembly from native antibodies by Endo-S2 catalyzed glycoengineering. In this strategy, Endo-S2 acts as either an endoglycosidase to release the heterogeneous glycans from IgG or a glycosynthase possessing the capability to recognize a disaccharide-linker-drug combination as a substrate and transfer it onto the deglycosylated IgG, thus achieving gsADCs in a one-step manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, either for the GTase-based or for the ENGase-based one, these approaches are restricted in substrate synthesis and dependent on two or more enzymes, a quite complicated and challenging procedure. To solve this issue, Wang et al, as well as our group, reported the one-step strategy for gsADCs assembly from native antibodies by Endo-S2 catalyzed glycoengineering. In this strategy, Endo-S2 acts as either an endoglycosidase to release the heterogeneous glycans from IgG or a glycosynthase possessing the capability to recognize a disaccharide-linker-drug combination as a substrate and transfer it onto the deglycosylated IgG, thus achieving gsADCs in a one-step manner.…”
Section: Introductionmentioning
confidence: 99%
“…However, either for the GTase-based or for the ENGase-based one, these approaches are restricted in substrate synthesis and dependent on two or more enzymes, a quite complicated and challenging procedure. To solve this issue, Wang et al, 17 as well as our group, 18 reported the one-step strategy for gsADCs assembly from native antibodies by Endo-S2 catalyzed glycoengineering.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, there were advances from site-specific antibody conjugation using transglycosylation. A one-pot reaction for deglycosylation and transglycosylation in antibody Fc was described using wild-type endoglycosidase from Streptococcus pyogenes of serotype M49 (Endo-S2) [ 54 , 55 ]. The enzyme was shown to efficiently introduce the functionalized disaccharide oxazolines carrying site-selectively modified azide in varied numbers, resulting in ADCs with a precise control of DAR ranging from 2 to 12 via a copper-free strain-promoted click chemistry.…”
Section: Overview Of Site-specific Antibody Conjugationmentioning
confidence: 99%
“…However, the established technology requires using two different enzymes, which may complicate CMC and production, including the separation of ADCs from enzymes. [93] To overcome this issue, several promising approaches were published: Wang's group [94,95] and Huang's group [96] reported remodeling glycans in one step directly from native mAbs by disaccharide LacNAc oxazolines, respectively. These approaches enable simplifying the preparation of glycan-mediated antibody conjugates and have applications in related manufacturing.…”
Section: Comparison Of Three Enzymatic Conjugation Processesmentioning
confidence: 99%